2016
DOI: 10.1007/s00502-015-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent plaster for accurate body temperature monitoring and investigations regarding EMI using near-field magnetic scan

Abstract: A wireless self-sufficient human body temperature monitoring system was designed using a 130 nm CMOS standard process. This miniaturized sensor grain enables significant cost advantages and impresses with its high level of integration. The RFID communication protocol ensures compatibility with state-of-the-art smart phones and tablets, thus facilitating point-of-care as well as end-user utilization. The biocompatible plaster enables cyclic measurements and also storage of the obtained data. In the range of 35°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As the only temperature is considered, this approach is useful only for highly temperature-sensitive products such as fresh food, dairies, etc. Another RFID-based temperature monitoring system is presented in [21]. The presented system is designed in form of the biocompatible plaster using 130 nm CMOS technology, powered by a rechargeable lithium-ion battery.…”
Section: Related Workmentioning
confidence: 99%
“…As the only temperature is considered, this approach is useful only for highly temperature-sensitive products such as fresh food, dairies, etc. Another RFID-based temperature monitoring system is presented in [21]. The presented system is designed in form of the biocompatible plaster using 130 nm CMOS technology, powered by a rechargeable lithium-ion battery.…”
Section: Related Workmentioning
confidence: 99%
“…This is referred to as tag diversity. In [11], a plaster operating over a few centimetres at the near field communication (NFC) frequency of 13.56 MHz was presented and in [12] the most efficient tag placement for two worn ultra high frequency (UHF) tags communicating with an external reader was studied using 3 mm thick textile slotted patch antennas. The study indicated that more than two tags of the slotted patch design were required to provide coverage all around the body.…”
Section: Introductionmentioning
confidence: 99%